2016
DOI: 10.1021/acs.jproteome.5b00796
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Site-Specific Phosphoproteomics of Trichoderma reesei Signaling Pathways upon Induction of Hydrolytic Enzyme Production

Abstract: The filamentous fungus Trichoderma reesei is used for industrial production of secreted enzymes including carbohydrate active enzymes, such as cellulases and hemicellulases. The production of many of these enzymes by T. reesei is influenced by the carbon source it grows on, where the regulation system controlling hydrolase genes involves various signaling pathways. T. reesei was cultivated in the presence of sorbitol, a carbon source that does not induce the production of cellulases and hemicellulases, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 42 publications
1
38
1
2
Order By: Relevance
“…Recently, a phosphoproteomic investigation of T. reesei exposed to sophorose and distiller’s spent grain showed that Tmk3 is phosphorylated under these cellulase-inducing conditions [64]. What’s particularly interesting is that Tmk3 was also the only MAPK that is found to be phosphorylated when exposed to sophorose or distiller’s spent grain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a phosphoproteomic investigation of T. reesei exposed to sophorose and distiller’s spent grain showed that Tmk3 is phosphorylated under these cellulase-inducing conditions [64]. What’s particularly interesting is that Tmk3 was also the only MAPK that is found to be phosphorylated when exposed to sophorose or distiller’s spent grain.…”
Section: Discussionmentioning
confidence: 99%
“…Production of galactaric acid was much higher in these 4 mL batch cultures than has previously been reported for flask cultures with filamentous fungi (around 4 g L −1 ; [8, 10]). The medium in the 24-well plates contained spent grain extract, which was expected to induce the CBH1 promoter [16], but not necessarily other promoters. Spent grain extract also provides organic nitrogen, resulting in a richer medium, which may contribute to the good conversion of d -galacturonic acid into galactaric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these conserved regions contain up to three continuous S/T phosphorylation sites. Moreover, phosphorylation of the peptide sequence extending from amino acids 387 to 402 (SSTTGSLAGGDLMDRM) at the C-terminus of Cre1 from T. reesei (Tr_Cre1) was identified with LC-MS/MS by Nguyen et al (2016).…”
Section: Phosphorylation Of Cre1mentioning
confidence: 99%
“…Meanwhile, it was assumed that phosphorylation of Cre1 in T. reesei affects its repressing activity on cellulase genes under CCR (Cziferszky et al, 2002;Nguyen et al, 2016).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation